Dificuldades para a implantação de softwares integradores de projeto (BIM) por usuários da cidade de Aracaju/Sergipe - Maciel, Marcelo Augusto Costa (2014)
CAD system is used in the development of a real estate projects since the 1990s. More recently, BIM has been implemented in this task. The aim of this work is to analyze what are the main difficulties to implement BIM in architecture and urban planning offices, offices that develop complementary designs and construction companies in cities of Northeast Brazil. These tools work on modeling of the building and bring a vast amount of information incorporated into the project, which helps in decision-making and minimizing wastes in real estate development. For this, the performance of architecture and urbanism offices, offices that develop complementary designs and construction companies in cities of Northeast was evaluated through structured interviews and documentary research. Interviews with companies in the Southeast, that already use the tool in order to understand the extent of the use of BIM in Brazil were also performed. It was searched the organizational structure, profile of the professionals involved, degree of implementation and the methodology used for the projects development. It´s been included the relationship with the complementary projects and actions were pursued that contribute to the waste reduction. It was found that there is strength in the adoption of BIM software, because who uses it in the projects development, presents the product to customers through CAD. It was also observed that designers, despite identifying some wastes in the development of their work, have no knowledge of lean principles, or how they could improve the development of their work. For the companies in the development and construction area, the initial research observed that, despite having knowledge of the lean construction concepts, also did not adopt the practice to develop their projects with BIM software. Since this is an extensive topic, this research it is restricted to the design and planning stages of the operations studied.It is expected that with a higher charge on the use of BIM by contractors or funding agencies, this resource will be used more often in cities of the Brazilian Northeast.